Implementation of Intelligent Automated Gate System with QR Code-An IOT System to help gate management - Hamid E.; Gee L.C.; Bahaman N.; Anawar S.; Ayob Z.; Malek A.A. (Science and Information Organization, 2024)
Indexed by WOS/Scopus/ERA